2014
DOI: 10.5455/2320-6012.ijrms20141128
|View full text |Cite
|
Sign up to set email alerts
|

Seizure in later life: an ode to the elderly

Abstract: INTRODUCTIONThe advances in the current medical science and technology have strived forward in increasing longevity of the population. Major economies in the worlddeveloping and developed alike are facing an ever increasing graying population with the inherent risk of morbidity and mortality. The combined endpoint of a mechanized and sedentary lifestyle added up with an increase in life span invites our acuity towards a fragile unbalanced segment of the society to whom we are obliged for what we are.Epilepsy i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…This case was in older age with misleading symptoms dissimilar to classic ones, e.g., defective visual field and fluctuating ataxia. New onset seizures in adulthood should not be overlooked because there may be usually an important lesion in the brain as its etiology especially vascular malformation [6,8]. Selective imaging in this lesion includes brain MRI and CT angiography [1,9].…”
Section: Discussionmentioning
confidence: 99%
“…This case was in older age with misleading symptoms dissimilar to classic ones, e.g., defective visual field and fluctuating ataxia. New onset seizures in adulthood should not be overlooked because there may be usually an important lesion in the brain as its etiology especially vascular malformation [6,8]. Selective imaging in this lesion includes brain MRI and CT angiography [1,9].…”
Section: Discussionmentioning
confidence: 99%
“…New-onset seizures in elderly people often has an underlying etiology, including cerebrovascular diseases, primary neuron degenerative disorders, intracerebral tumors and traumatic head injury [5]. Stroke and other cerebrovascular diseases are the most important risk factors for new-onset epilepsy and seizures in the elderly, which account for 30%-50% in all identified etiologies [61][62][63]. Stroke is an important cause of epilepsy and seizures [64].…”
Section: Introductionmentioning
confidence: 99%
“…Stroke and other cerebrovascular diseases are the most important risk factors for new-onset epilepsy in the elderly, which account for 30%–50% in all identified causes. 10 , 15 17 In general, epilepsy can occur at the time or after stroke, or can be an early clinical manifestation of cerebrovascular diseases. Studies have reported that the risk of developing epilepsy in the first year after a stroke increases by 20 times.…”
Section: Introductionmentioning
confidence: 99%